4, 4′-Dimethyl-2, 2′-bithiazole: Potent co-former in coordination compounds. (24th November 2016) - Shahbazi-Raz, Farsheed; Notash, Behrouz; Amani, Vahid; Safari, Nasser
Graphical Abstract: The ability of the 4, 4′-dimethyl-2, 2′-bithiazole (4dm2bt) ligand to act as a second-sphere co-former in coordination compounds is investigated through the preparation of a series of iron complexes. The driving forces for the presence of the 4dm2bt molecule as a second-sphere co-former ligand are not only several types of non-covalent interactions with first-sphere coordination ligands or counter anions, but also its low coordination ability for participating as a primary ligand in comparison with the N - N ′-chelating ligands used. Abstract: The ability of the 4, 4′-dimethyl-2, 2′-bithiazole (4dm2bt) ligand to act as a second-sphere co-former in coordination compounds is investigated through the preparation of a series of iron complexes. In this regard, the self-assembly process of FeCl3 ·6H2 O or FeCl3 in the presence of several N - N′ -chelating ligands and 4dm2bt was investigated. The complexes [Fe(bipy)(H2 O)Cl3 ][4dm2bt] (1 ), [Fe(bipy)(CH3 OH)Cl3 ][4dm2bt]0.5 (2 ), [Fe(4, 4′-dmbipy)3 ][FeCl4 ]2 [4dm2bt]0.5 (3 ), [Fe(phen)2 Cl2 ][FeCl4 ][4dm2bt]0.5 (4 ) and [Fe(5-mephen)2 Cl2 ][FeCl4 ][4dm2bt]0.5 (5 ), which contain the 4dm2bt co-former, were prepared (bipy = 2, 2′-bipyridine, 4, 4′-dmbipy = 4, 4′-dimethyl-2, 2′-bipyridine, phen = 1, 10-phenanthroline, 5-mephen = 5-methyl-1, 10-phenanthroline). The driving forces for the presence of 4dm2bt as a second-sphere co-former ligand are not only several types of non-covalent interactions with the first-sphere coordination ligands or counter anions, but also its low coordination ability for participating as a primary ligand in comparison with the N - N′ -chelating ligands used.